Cardiac tamponade as the initial manifestation of pulmonary adenocarcinoma - Letonja, Mitja (Radiology and oncology (Ljubljana), 2007)
Background. Neoplastic pericarditis can be presented as acute pericarditis, pericardial effusion, effusive-constrictive pericarditis or cardiac tamponade.For the majority of patients, a clinical manifestation of neoplasticpericarditis is absent or remains unrecognised during their life. Case report. A 69-year-old non-smoking woman with acute dyspnoea, tachycardia,jugular venous distension, hepatomegaly and right side pleural effusion was presented in the emergency department. The roentgen picture of the chest confirmed pleural effusion and revealed enlarged heart. An emergencyechocardiogram established the diagnosis of cardiac tamponade. The patient improved immediately after the therapeutic pericardiocentesis. Cytology of pericardial fluid confirmed malignant glandular cells, consistent with metastatic adenocarcinoma. A computed chest tomography showed a right side pleural effusion and a solitary round lesion in the right lower lobe of the lung. Bronchoscopy with fundoscopic lung biopsy and brushing revealed adenocarcinoma. Conclusions. Cardiac tamponade as the initial manifestation ofmalignancy is rare and rare is also malignant pericardial effusion due the adenocarcinoma of the lung in a non-smoking woman. The presented patient had one of the longest survival reported in literature despite a limited life expectancy regardless of the treatment in the patient presented with neoplastic pericarditis.
Keywords: Adenocarcinoma; Adenokarcinom; Aged; Cardiac Tamponade; Diagnosis; Lung Neoplasms; onkologija; Pericardial Effusion; perikarditis; Perikardni izliv; Pljučne novotvorbe; rak (medicina); Srce, tamponada; Starostniki